Enumeration of Salmonella spp., Salmonella Typhi and Salmonella Typhimurium in fruit juices - Jeremiah, Erica Diana; Pui, Chai Fung; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Salmonella has caused foodborne illnesses globally and it has been a rising threat on fresh produce. The objective of this study was to determine the prevalence and concentration of Salmonella spp., Salmonella Typhi and Salmonella Typhimurium in freshly prepared fruit juice sold at hawker stalls. Analysis was conducted by employing most probable number-polymerase chain reaction (MPN-PCR). A total of 50 freshly prepared fruit juices were examined and the prevalence of Salmonella spp., Salmonella Typhi and Salmonella Typhimurium in the fruit juices were 34%, 20% and 10%, respectively, with an estimated microbial load varying from 0 to 42 MPN/g. Of the five different fruits, carrot juice had the highest prevalence of Salmonella spp. (60%) and Salmonella Typhi (40%). However, Salmonella Typhimurium was detected in apple (30%), orange (10%) and starfruit juice (10%). Factors contributing to the presence of Salmonella were cross-contamination and poor sanitation practice. Besides, negligence on temperature and storage time also led to the growth of Salmonella. Proper monitoring and risk assessment are needed in order to establish control measures to ensure the quality and safety of fruit juices in Malaysia.